(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The purpose of this study was to investigate the relationship between using active learning strategies and burnout for secondary schools teachers. For this purpose, the researcher prepared a questionnaire to measure the degree of using active learning strategies, and Maslach scale of burnout. The sample consisted of (218) teachers in Latakia City. The descriptive approach was used. Teachers` responses were analyzed by (SPSS). The results showed: teachers of secondary schools use corporation learning strategies and discussion strategies highly whereas some active learning strategies such as problem solving and brainstorming are used weakly. In general, the participants use active learning strategies moderately. As for job burnout, the results showed that teachers have scored high average on the scale of burnout. There is a negative correlative statistical relationship between using active learning strategies and burnout for secondary schools teachers. Many suggestions were introduced in the light of results: make training courses in field of using modern learning strategies.